Debt And Happiness: A Generalized Order Logit Analysis - Edy Purwanto; Rudi Purwono; Ni Made Sukartini (Universitas Airlangga, 2025)
Objective: Financial literacy can influence borrowing attitudes and behaviors. Low financial literacy among Indonesians may impair debt manageability and lead to psychological distress. This empirical research aimed to analyze the effects of debt on happiness in Indonesia. Methods: This study used cross-sectional data from the 2007 Indonesia Family Life Survey (IFLS). Happiness was measured on a four-point ordinal scale, namely very unhappy (1), unhappy (2), happy (3), and very happy (4). Given the nature of the dependent variable, a generalized ordered logit model was applied to estimate the relationship between debt and happiness. This approach is well-suited to address the study objective by capturing varying effects across different levels of happiness. Findings: Results showed a significant negative relationship between debt and happiness (coefficient = -0.145, p < 0.01). The marginal effect indicated that debt reduced the likelihood of being happy and very happy by -0.20% and -0.83%, respectively. Depression had the strongest negative impact (-5.67%), while marriage (4.03%), household economic adequacy (3.40%), health care (2.31%), and physical health (1.99%) were the positive contributors. Originality/Value: This study contributed to the limited research examining the link between debt and well-being in developing economies, focusing on Indonesia’s socioeconomic and cultural context. Practical/Policy implication: Financial literacy needs to be enhanced to improve borrowing decisions and debt management among Indonesians. Strengthening financial education programs and regulating non-formal lenders are essential to prevent exploitative lending practices. Moreover, integrating debt awareness into mental health programs and disseminating information through mass and social media can help mitigate the psychological impact of debt.